Análise multicriterial das preferências de gestores e das decisões nas operações logísticas de uma empresa do setor químico - Forneck, Marcelo (Universidade do Vale do Rio do Sinos, 2008)
The context of human organizations, researchers and professionals has considered a lot the process of performance evaluation, once it provides to the company to identify differentials which can help them to be more competitive. Therefore, the fast development of products, information integration, advanced communication technologies, customization of products and coordination of supply nets, is forcing the companies to take faster decisions. The use of qualitative method of support to the decision, may contribute to reduce risks and manage uncertainties in this faster decision taking. The objective of the present work was to present a case study in which was developed and tested an analysis method of the preferences of the internal entrepreneurial logistic operations managers. The result of the method’s application was compared to the result of some decisions taken in the company. The research methodology reckoned with a focus group formed by the company’s internal logistic managers, involving the supply, prod
Keywords: análise multicriterial; avaliação de desempenho na logística interna; tomada de decisão; critérios de competição; analytic hierarchy process (AHP); decision taking; internal logistics performance evaluation; multi criteria analysis; competitiveness criteria; Engenharias